Ethnic Background Is a Potential Barrier to Living Donor Kidney Transplantation in Canada: A Single-Center Retrospective Cohort Study. Issue 4 (April 2017) - Mucsi, Istvan; Bansal, Aarushi; Famure, Olusegun; Li, Yanhong; Mitchell, Margot; Waterman, Amy D.; Novak, Marta; Kim, S. Joseph
Abstract : Background: We examined if African or Asian ethnicity was associated with lower access to kidney transplantation (KT) in a Canadian setting. Methods: Patients referred for KT to the Toronto General Hospital from January 1, 2003, to December 31, 2012, who completed social work assessment, were included (n = 1769). The association between ethnicity and the time from referral to completion of KT evaluation or receipt of a KT were examined using Cox proportional hazards models. Results: About 54% of the sample was white, 13% African, 11% East Asian, and 11% South Asian; 7% had "other" (n = 121) ethnic background. African Canadians (hazard ratio [HR], 0.75; 95% CI: 0.62-0.92]) and patients with "other" ethnicity (HR, 0.71; 95% CI, 0.55-0.92) were less likely to complete the KT evaluation compared with white Canadians, and this association remained statistically significant in multivariable adjusted models. Access to KT was significantly reduced for all ethnic groups assessed compared with white Canadians, and this was primarily driven by differences in access to living donor KT. The adjusted HRs for living donor KT were 0.35 (95% CI, 0.24-0.51), 0.27 (95% CI, 0.17-0.41), 0.43 (95% CI, 0.30-0.61), and 0.34 (95% CI, 0.20-0.56) for African, East or South Asian Canadians and for patients with "other" ethnic background, respectively. Conclusions: Similar to other jurisdictions, nonwhite patients face barriers to accessing KT in Canada. This inequity is very substantial for living donor KT. Further research is needed to identify if these inequities are due to potentially modifiable barriers. Abstract : Access to kidney transplantation (KT) is significantly reduced for all ethnic groups assessed compared to Caucasian Canadians, and this is primarily driven by differences in access to living donor KT. Further research is needed to identify the causes of inequities. Supplemental digital content is available in the text.